BRAND EQUITY STRATEGY IN BUILDING BRAND IDENTITY FOR ACRYLIC FLOWER BOARD PRODUCTS - Cecilia Indah Hapsari; Dida Maulidya Al Afshana; Sudarmiatin Sudarmiatin; Ita Prihatining Wilujeng (Journal of Economic, Bussines and Accounting (COSTING), 2025)
The research problem is motivated by increasing business competition that requires MSMEs to strengthen brand identity and consumer trust through effective brand management. This study uses a qualitative approach with a case study method. Data collection techniques were carried out through interviews with business owners, direct observation, and documentation. Data analysis uses the Miles, Huberman, and Saldana model, which includes the stages of data condensation, data presentation, and conclusion drawing. The results show that Miracle Florist has successfully implemented the five main components of brand equity according to Aaker (1991): brand awareness, brand association, perceived quality, brand loyalty, and other proprietary. Brand awareness development is carried out through consistent digital promotions on Instagram and TikTok platforms. Brand association is reflected in the consistency of the logo, colors, and brand name. Perceived quality is maintained through premium product quality and responsive service. Brand loyalty is formed from customer satisfaction and word of mouth promotion. In addition, other proprietary rights are realized through legal protection of brand identity through Intellectual Property Rights (IPR). This study concludes that the implementation of brand equity strategy is able to strengthen product identity, increase consumer trust, and build sustainable brand loyalty at Miracle Florist MSME.